Selenoglicolicamidas: síntese, caracterização e avaliações das atividades antimicrobiana, leishmanicida e citotóxica em células tumorais - Souza, Helivaldo Diógenes da Silva (2018)
In the search for new synthetic compounds and the development of new drugs, organoselenium compounds have been prominent in the last decades, mainly because they present a wide range of biological activities such as: antibacterial, antiviral, antifungal, anticancer, anti-inflammatory, antinociceptive, etc. In this work, we describe the synthesis of selenoglicolicamides, the antimicrobial, leishmanicide and cytotoxicity studies of the compounds. Selenoglycolicamides were obtained in yields between 70-80% and were characterized by IR, 1H and 13C NMR spectroscopic techniques. In the in vitro antimicrobial evaluation, the selenoglycolicamides presented activities against the different strains of Staphylococcus aureus with minimum inhibitory concentration (MIC) in the range of 16-256 µg/mL, highlighting the compounds HSe-01, HSe-06, HSe-09 that presented an MIC between 16-64 µg/mL. In the antibacterial evaluation against tetracycline resistant Staphylococcus aureus by modulating efflux pump resistance, selenoglycolicamides presented a potential adjuvant for the antibiotic, presenting a reduction factor of tetracycline MIC up to 512 times. In the antifungal activity, only HSe-01 and HSe-09 compounds exhibited inhibitory activity against Candida strains with MIC between 512-1024 µg/mL. The leishmanicidal evaluation in L. amazonensis promastigote cells shows that selenoglycolicamides with halogens in their structures showed IC 50 of less than 10 µM, especially for compound HSe-05 with an IC50 of 5.46 µM. In the cytotoxic evaluation against tumor cells, the selenoglycolicamides that stood out the most in the inhibition of cell growth (IC%) were: HSe-02 and HSe-07 with 49% inhibition against the MCF-7 lineage; HSe-02 and HSe-05 with 100% inhibition against the HEp-2 lineage and HSe-05 with 99.56% inhibition in the HL60 lineage. In the determination of the IC50 in the HL-60 tumoral lineage, selenoglicolicamide HSe-02 presented an IC50 of 3.42 µg/mL.